Educating All of the Children of All of the People: Will School Choice Help or Hinder? - Van D. Mueller (Educational Considerations, 1994)
In most cases better-off Americans simply have a narrow view of what they are doing… They do not want poor children to be harmed; they simply want the best for their own children.